Techno-economic optimization of hybrid renewable electrification systems for Malawi's rural villages. Issue 1 (1st January 2021) - Malanda, Clement; Makokha, Augustine B.; Nzila, Charles; Zalengera, Collen
Abstract: Renewable energy systems provide a resilient access pathway to affordable and sustainable energy for millions of people in regions with no or undeserved grid. In this work, a multi-objective Hybrid Optimization Model for Electric Renewables (HOMER) software has been applied to design and assess the techno-economic feasibility of Hybrid Renewable Energy Systems (HRESs) for Malawi's off-grid communities. The study targeted the use of decentralized photovoltaic (PV), wind, diesel generator, and battery storage technologies to electrify three villages of Chigunda, Mdyaka, and Kadzuwa, which had estimated daily electrical energy peak demands of 14.53, 8.09, and 6.40 kW, respectively. Wind and solar resource data were used as inputs to generate multiple combinations of energy systems in HOMER. The sensitivity of the output systems was tested by varying the wind velocity and diesel pump prices. The optimization results showed that for Chigunda, the optimal configuration comprised PV-wind-battery, while for Mdyaka and Kadzuwa, the PV-battery combinations were ideal. In all the cases, the optimal systems were more sensitive to changes in wind velocity. The systems were, however, found to be infeasible economically as the costs of energy were higher than the per kilowatt-hour cost of US 0.120 for electricity in Malawi.